2016
DOI: 10.1001/jamainternmed.2015.8042
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Geriatric Assessment and Transitional Care in Acutely Hospitalized Patients

Abstract: IMPORTANCE Older adults acutely hospitalized are at risk of disability. Trials on comprehensive geriatric assessment (CGA) and transitional care present inconsistent results. OBJECTIVE To test whether an intervention of systematic CGA, followed by the transitional care bridge program, improved activities of daily living (ADLs) compared with systematic CGA alone. DESIGN, SETTING, AND PARTICIPANTS This study was a double-blind, multicenter, randomized clinical trial conducted at 3 hospitals with affiliated home … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
107
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(111 citation statements)
references
References 36 publications
0
107
0
4
Order By: Relevance
“…The HOME intervention was assessed in a randomized control trial (RCT) involving 400 older patients with varied medical conditions treated in five acute Australian hospitals [28]. Consistent with other evidence-based interventions [30,31], no between-group differences were found between HOME compared to the in-hospital occupational therapy consultation on the main outcomes (independence in ADL, participation in life roles, and hospital and ED readmissions) in this trial [28].…”
Section: Introductionmentioning
confidence: 75%
“…The HOME intervention was assessed in a randomized control trial (RCT) involving 400 older patients with varied medical conditions treated in five acute Australian hospitals [28]. Consistent with other evidence-based interventions [30,31], no between-group differences were found between HOME compared to the in-hospital occupational therapy consultation on the main outcomes (independence in ADL, participation in life roles, and hospital and ED readmissions) in this trial [28].…”
Section: Introductionmentioning
confidence: 75%
“…Information provided about the exact content of the instrument varied between CGAs. For five CGA instruments, the content of the CGA was available in (the appendix of) the original study or in a study cited in the original study (Buurman et al, ; Buurman, Parlevliet, van Deelen, de Haan, & de Rooij, ; Fleischer et al, ; Ruikes et al, , ; Stijnen, Duimel‐Peeters, et al, ; Suijker et al, , ). For the other CGAs, the original study did not provide or only partially provided the exact content of the CGA nor referred to other papers describing this information.…”
Section: Resultsmentioning
confidence: 99%
“…This Dutch program aimed to improve care and support for older people through funding of several research and implementation projects focused on developing a more proactive and integrated health and social care system for frail older people (Hoogendijk, ; Lutomski et al, ). Nine of these projects, with eight different CGA instruments and procedures, were included in this study (Blom et al, ; Buurman et al, , ; Daniels et al, ; Hoogendijk et al, ; Looman et al, , ; Metzelthin et al, , ; Muntinga et al, ; Ruikes et al, , ; Spoorenberg et al, , ; Stijnen, Duimel‐Peeters, et al, ; Suijker et al, , ; Uittenbroek et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…A closer look at the performance of the intervention showed that low treatment fidelity (<50%) played a major role in the ineffective implementation of the PReCaP (de Vos et al, 2013). The results of three other projects within the Dutch National Care for the Elderly Program, in the clinical setting as well as in primary care, demonstrate that multidisciplinary 'evidence based' interventions for frail elderly are executed with limited fidelity and few minor positive effects (Fabbricotti et al, 2013;Asmus-Szepesi et al, 2015;Buurman et al, 2016). Treatment fidelity issues are caused by various factors, such as the complexity of the projects (Metzelthin et al, 2013), limited attention for implementation, lack of geriatric knowledge and inadequate interdisciplinary communication of patient information (de Vos et al, 2013;Hartgerink, 2013).…”
Section: Discussionmentioning
confidence: 99%